THE APPLICATION OF POLITENESS STRATEGIES AMONG TEACHER AND STUDENTS IN CLASSROOM INTERACTION AT SMA 1 PAMBOANG, MAJENE - Sudirman, Andi Mangnguntungi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
This research aims to find out the politeness strategies between the teacher and students in the classroom. This research employed descriptive qualitative. The participants of this research were two teachers and his/her students at Class XI IPS 1, XI IPA 1 and XII IPS 1 at SMA 1 Pamboang, Majene in the academic year 2012/2013. The data taken from this research are the utterances produced by the teacher and the students during the classroom discussion went out.Â  It was discovered that the politeness strategies which is expressed by the teachers to the students in SMA 1 Pamboang, Majene there were three politeness strategies that as proposed by Brown and Levinson in this research. They are Bald-on Record strategy, Positive Politeness strategy and negative politeness strategy among students, teacher and the observer. So, the four politeness strategy of Brown and Levinson do not found in the classroom interaction among students and teachers in SMA 1 Pamboang, Majene. The uses of possessive pronouns ânyaâ and âmuâ are mostly to show the politeness strategies which is expressed by the teachers to the students.